Investigation of Carbon Nanotube Grafted Graphene Oxide Hybrid Aerogel for Polystyrene Composites with Reinforced Mechanical Performance - Sun, Yanzeng (Polymers (Basel), 2021)
The rational design of carbon nanomaterials-reinforced polymer matrix composites based on the excellent properties of three-dimensional porous materials still remains a significant challenge. Herein, a novel approach is developed for preparing large-scale 3D carbon nanotubes (CNTs) and graphene oxide (GO) aerogel (GO-CNTA) by direct grafting of CNTs onto GO. Following this, styrene was backfilled into the prepared aerogel and polymerized in situ to form GO–CNTA/polystyrene (PS) nanocomposites. The results of X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy indicate the successful establishment of CNTs and GO-CNT and the excellent mechanical properties of the 3D frameworks using GO-CNT aerogel. The nanocomposite fabricated with around 1.0 wt% GO-CNT aerogel displayed excellent thermal conductivity of 0.127 W/m∙K and its mechanical properties were significantly enhanced compared with pristine PS, with its tensile, flexural, and compressive strengths increased by 9.01%, 46.8%, and 59.8%, respectively. This facile preparation method provides a new route for facilitating their large-scale production.